On the information content of the fama and French factors in the UK - Sulaiman Mouselli; Maria Michou; Andrew Stark (The University of Manchester, Manchester Business School, 2008)
This study explores the information content of HML and SMB by linking the Fama-French factors to shocks in the state variables which predict future investment opportunities. It shows that the HML factor contains information about shocks to default spread. Moreover, the Fama-French model explains the cross-section of average returns on portfolios sorted on size and book-to-market ratio better than both a model that includes shocks to the state variables and a model that includes news related to future industrial production growth in addition to the market factor. Furthermore, when loadings on HML and SMB are present in the model, loadings on shocks to default spread lose its explanatory power for the cross-section of returns. The results provide economic interpretation for the empirical success of HML factor but different from the US evidence that shocks to state variables subsume Fama-French factors.
Keywords: 330; Kapitalanlage; Portfolio-Management; Capital Asset Pricing Model